Psychosocial factors at work and myocardial infarction among men in Kaunas, Lithuania - Malinauskiene, Vilija; Theorell, Töres; Grazuleviciene, Regina; Azaraviciene, Ada; Obelenis, Vytautas; Azelis, Vidmantas (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'The association between job demand and job control and first nonfatal myocardial infarction was studied among the 25- to 64-year-old male population in Kaunas, Lithuania. ' ' METHODS ': 'A translation of the Swedish version of the demand–control questionnaire was used. Both psychosocial work characteristics as independent risk factors and the possible effects of traditional risk factors (smoking, arterial hypertension, overweight) were analyzed in a case–control study among 203 men diagnosed in 2001–2002 with a first nonfatal myocardial infarction (cases) and 287 men randomly selected as controls. A logistic regression analysis was used to estimate the odds ratio for developing myocardial infarction in relation to self-reported job demand and job control. Possible confounders (age, marital status, education, type of occupation, smoking, blood pressure, body mass index) were controlled. ' ' RESULTS ': 'The adjusted odds ratio was 0.56 [95% confidence interval (95% CI 0.37–0.85)] and 1.53 (95% CI 1.04–2.38), for demand and control, respectively. That for workers with low demand and low control was 1.89 (95% CI 0.99–3.60) as compared with low demand and high control. The risk of myocardial infarction for men in passive jobs (low demand and low control) was twofold that of the other respondents. ' ' CONCLUSIONS ': 'The association between low job control and the risk of myocardial infarction was found to be consistent with research in western populations. In contradiction, however, to findings in western studies, low demand, rather than high demand proved to be a risk factor for 25- to 64-year-old men. Employees in passive jobs had the highest risk.
Keywords: case-control study; demand–control questionnaire; job control; job demand; Lithuania; logistic regression; male; myocardial infarction; psychosocial factor; psychosocial job category; risk assessment; risk factor; work